(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Antibiotics constitute a critical class of medications, essential for treating bacterial infections and averting life-threatening complications. Nevertheless, their misuse—including inappropriate indications, suboptimal dosing, excessive durations, and self-medication—represents a profound global public health threat, exacerbating antimicrobial resistance. Objectives: To assess the knowledge, attitudes, and practices (KAP) concerning rational antibiotic use among second- and third-year Pharmacy students at Ca Mau Medical College in 2025, and to identify associated factors. Subjects and Methods: A cross-sectional descriptive study was conducted among 343 second- and third-year Pharmacy students at Ca Mau Medical College in 2025, employing an anonymous, self-administered questionnaire. Results: The prevalence of correct knowledge, positive attitudes, and appropriate practices regarding rational antibiotic use was 70.4%, 59.2%, and 73.2%, respectively. Academic year and the consulted individual for antibiotic advice during illness were associated with knowledge and practices (p < 0.05); ethnicity correlated with attitudes; and the primary information source for antibiotic use predicted rational practices. Conclusions: While knowledge and practices of rational antibiotic use among students are satisfactory, attitudes remain suboptimal. Notably, some students persist in self-purchasing and using antibiotics without adhering to recommended dosages and durations. Institutions should prioritize curricula integration of antibiotic stewardship principles, emphasizing common misuse errors to enhance attitudes and practices.